Benefits, Challenges, and Practices on the Utilization of Digital Platform among Secondary School Teachers in A Division - Mauricio-Garcia, Sheila Marie (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The utilization of digital platforms in education has become increasingly prevalent, particularly among secondary school teachers. This study aims to explore the benefits, challenges, and practices associated with the incorporation of digital platforms in the teaching methods of secondary school teachers within a specific division. Teachers experience enhanced engagement and interaction within their classrooms, resulting in improved student participation and comprehension. Moreover, digital platforms offer flexibility in delivering instructional materials, accommodating diverse learning styles and paces. However, alongside these benefits, teachers encounter notable challenges. Technical barriers, such as limited access to devices and internet connectivity, hinder the seamless integration of digital platforms. Privacy and security concerns, coupled with the need for digital literacy skills, further complicate the adoption process. Moreover, the transformation of traditional teaching methods to suit digital platforms necessitates time and effort. In this context, various practices emerge among secondary school teachers. Effective integration of digital platforms requires strategic planning, encompassing content creation, delivery modes, and assessment methods. Collaborative approaches, where teachers share experiences and resources, mitigate challenges, and foster professional growth. Furthermore, adapting to students' digital fluency, tailoring content for different subjects, and harnessing interactive features prove crucial to successful implementation. By examining the benefits, challenges, and practices related to digital platform utilization, this study contributes insights that can inform educational policies, professional development programs, and instructional strategies. The findings underscore the importance of acknowledging challenges while harnessing the opportunities digital platforms offer to enhance the teaching and learning experience in secondary education.